2022
DOI: 10.1016/j.psj.2021.101566
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary n-3 fatty acids sources on performance and formation of omega-3 in egg of laying hens: a meta-analysis

Abstract: A meta-analysis was performed to evaluate the effects of supplementary n-3 polyunsaturated fatty acids ( PUFA ) sources in the diet on the formation of some important n-3 PUFA contents in eggs and to assess factors contributing to the conversion efficiency of omega-3 in laying hens. A dataset was constructed from 34 studies examining the impact of dietary inclusion with ingredients rich in n-3 PUFA on fatty acids profile and production performance of laying hens. The eligibility criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…These results indicate a gradual increase in yolk ω-3 deposition, reflecting the dietary increase in ω-3 intake by laying hens. In accordance with the present results, the fatty acid profile of the egg yolks of hens receiving diets with vegetable oils changes according to the dietary oil fed [4,[53][54][55][56][57]. Moreover, a gradual effect of the ω-6/ω-3 PUFA ratio in feed and egg yolk (15.99 and 2.34; 16.72 and 4.34, respectively) revealed that 3% of tuna oil supplementation was a good predictor of the ω-6/ω-3 PUFA ratio in yolk [55].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results indicate a gradual increase in yolk ω-3 deposition, reflecting the dietary increase in ω-3 intake by laying hens. In accordance with the present results, the fatty acid profile of the egg yolks of hens receiving diets with vegetable oils changes according to the dietary oil fed [4,[53][54][55][56][57]. Moreover, a gradual effect of the ω-6/ω-3 PUFA ratio in feed and egg yolk (15.99 and 2.34; 16.72 and 4.34, respectively) revealed that 3% of tuna oil supplementation was a good predictor of the ω-6/ω-3 PUFA ratio in yolk [55].…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the ω-6/ω-3 PUFA ratio in the egg yolk is directly related to the type of oil (soybean vs. linseed) and ω-6/ω-3 ratio (10.17 vs. 0.83) [56]. Irawan et al [57] reviewed the published literature and revealed a stepwise positive relationship among the levels of α-linolenic acid, total ω-3 PUFA, and the dietary ω-6/ω-3 ratio with the formation of EPA, DHA, total ω-3 PUFA, and the ω-6/ω-3 ratio in the eggs with various magnitudes. The intercept and the slope estimated for the dietary composition of ω-3 PUFA were 15.12 and -0.15, respectively, on ω-3-PUFA in eggs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intake of marine food for our population was low, and the plasma DHA had a strong correlation with animal food products in this study, especially for eggs. Eggs with a higher content of phospholipids offered enriched DHA, and its DHA was easily absorbed due to the high DHA content of sn-2 in phospholipids [ 41 , 42 ]. Furthermore, there were different dietary assessment methods, population characteristics, and variations in intake.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the interaction, the same formula as above was employed but involving other covariates in the data, i.e., the type of livestock and the inoculation method. This model was assessed linearly as an interaction effect [ 26 ]. As for the quadratic model, when the results were not significant, the linear model was maintained.…”
Section: Methodsmentioning
confidence: 99%